Les méthodes de rééducation au Mont-Saint-Antoine de Montréal - Provençal, Roland (Université Laval, 1954)
Keywords: Délinquance; Enfants; Mont-Saint-Antoine

A Quantitative Study of Book Circulation: The Library of the Institut Canadien de Montréal - Harvey, Louis-Georges; Olsen, Mark (Historical Methods, 1985)
Number: 3
Keywords: Institut canadien

Modeling Residential Mobility in Montreal, 1860-1900 - Gilliland, Jason A. (Historical Methods, 1998)
Number: 1
Keywords: Famille; Logement; Mobilité résidentielle

Occupations and Residential Spaces in 19th Century Montreal - Olson, Sherry (Historical Methods, 1989)
Number: 2

Influence des méthodes de perspectives de population sur les résultats: l'exemple des migrations à Montréal - Mongeau, Jaël (Université de Montréal, 1977)

Women Prisoners and Modern Methods of Prison Control: A Comparative Study of Two Canadian Women's Prisons - Watson, Catherine M. (Université McGill, 1980)
Keywords: Femmes; Prisons

Histoire des programmes de télévision: essai méthodique appliqué aux cinq premières années de CBFT-Montréal, 1952-1957 - Laurence, Gérard (Université Laval, 1978)
Keywords: Télévision

"Du châssis à la machine à mouler": transformation des méthodes de production dans l'industrie canadienne du moulage, au cours de la seconde moitié du XIXe siècle - Bischoff, Peter (Material History Review / Revue d’histoire de la culture matérielle, 1995)
Number: 1
Keywords: Mouleurs

Église Unie St. James - Charowska, Ewa M. (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Méthodistes; Patrimoine; Église Unie

Estimation de la valeur économique des ressources en eaux souterraines de la région située au nord de Montréal : application de l'approche contingente et de la méthode des coûts évités - Martin, Michel (Université du Québec Institut national de la recherche scientifique, 1999)

Essai d'une méthode d'analyse typo-morphogénétique de l'information du bâti par le loti: les îlots et les sections de rue du quartier Saint-Jean-Baptiste à Montréal - La Rue, Pierre (Université de Montréal, 1987)
Keywords: Quartiers; Saint-Jean-Baptiste (village)

Quelques méthodes d'évaluation de la structure industrielle d'une région et ses changements comme instrument de l'analyse régionale, appliquée aux secteurs manufacturiers dans deux régions canadiennes: Montréal et Toronto - Siggel, Eckhard (Université de Montréal, 1971)

Chronicles of the St. James Methodist Church, Montreal, From the First Rise of Methodism in Montreal to the Laying of the Corner-Stone of the New Church on St. Catherine Street - Jaques, G. E. (William Briggs, 1888)
Keywords: Méthodistes; Protestants; St. James Methodist

The People of St. James, Montreal, 1803-1894 - Mair, Nathan (St. James United Church, 1984)
Keywords: Méthodistes; Protestants; St. James Street Methodist Church

The Urbanization of Nature: Water Networks and Green Spaces in Montreal - Dagenais, Michèle (Method and Meaning in Canadian Environmental History, 2009)
Keywords: Aqueduc; Parcs; Égouts

Domes & Towers (The Westmount Historian, 2013)
Number: 1
Keywords: Anglicans; Baptistes; Emanu-el (temple); Juifs; Méthodistes; Presbytériens; Protestants; Églises

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens